Ovulation and rate of implantation following unilateral ovariectomy in mice - Koushik Bhattacharya (Wolters Kluwer Medknow Publications, 2013)
Objectives: Removal of an ovary of any side of the body is called the unilateral ovariectomy (ULO). ULO models are used to analyze the existence of functional and physiological asymmetries between the ovaries, including the ovum implantation. Materials and Methods: ULO was done in mice without any specification on their stages of the estrous cycle. The animals were mated between 3 rd and 15 th day after ULO to observe the consequence of ULO on ovulation and ovum implantation. Results: Ovulation and number of implantation were decreased in proportion to single contralateral ovary if the animals were mated within 36 hrs of ULO. It resulted in increased weight of contralateral ovary due to hypertrophy, and also in compensatory ovulation, formation of corpus luteum (CL) that reached a peak after 14 th and 15 th day of ULO (sacrificed on 5 th day of pregnancy i.e., 19 th and 20 th day of ULO) compared to animals undergone sham-surgery. Numbers of implantations were also increased progressively on the contralateral ovarian side and get to a peak after similar days of compensation. Discussion and Conclusion: Following ULO, the remaining ovary started to compensate within 5 th to 6 th day of ULO even during pregnancy. Ovarian histology also showed increased formation of CL which is a marker of rate of ovulation.